(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article substantiates that the development of information technologies, the growing capabilities of computer technology and its spreading into all spheres of human life led to the use of information and communication technologies in the field of education. Modern pedagogues must orient themselves in colossal flows of information, be capable of its critical analysis, generalization, synthesis and application in pedagogical activities. In order to solve these problems, it is necessary to form informative competence based on critical thinking in future teachers. The purpose of the article is a theoretical study of critical thinking as a basic component in the structure of IT competence of modern teachers. To determine the theoretical foundations of the researched phenomenon, a set of interrelated research methods was used, in particular, the methods of analysis and synthesis, comparison, classification and generalization of scientific approaches to the research problem, presented in philosophical, sociological, psychological, and pedagogical sources. Research results. Today, all types of pedagogical activities of teachers are directly related to information and technological competences, the implementation of which requires critical thinking. Critical thinking is considered simultaneously as a process - the process of assessing the correctness and reliability of information, based on its correlation with available information, scientific titles, the formed scientific picture of the world, and as a result - the formed integrative ability or complex of skills. Clarifying the concept of informatics competence, emphasis is placed on its manifestation in the readiness to apply pedagogical knowledge, abilities and skills, as well as the means of information and communication technologies for searching, critical analysis and synthesis of information, solving complex tasks in professional and subject areas. The ability to analyze and select the necessary information is one of the key skills in the conditions of informatization of society, and the level of this skill is determined by the level of development of critical thinking.